PEMETAAN EKOSISTEM INOVASI DI PERGURUAN TINGGI - Zulfatun Najah, Aji Hermawan Sapta Raharja, Elisa Anggraeni (Jurnal Teknologi Industri Pertanian, 2018)
Innovation ecosystem mapping is a method to identify positions and roles of stakeholders. This research was an initial stage of research of building innovation ecosystem in higher education institution. Mapping of stakeholder’s roles was conducted by classifying stakeholder’s role based on framework of process innovation that include idea generation, research and development and commercialisation. This research used case study research design. Bogor Agricultural University (IPB) was choosen as object study because it contributed as the most active innovation producer during 2009-2016 period according to LIPI Indonesia Business Innovation Center. Data collection is done through interview and collecting related document such as Standard Operation Procedure (SOP). After conducting studies, there were 13 activities related to innovation process conducted by stakeholders which determine the development performance of IPB innovation ecosystem. Based on overlapping analysis, there were similarities of roles in innovation management of IPB that werefacilitating research cooperation, incubating, patenting and disseminating innovation. Based on gap analysis, all of commercialisation process stage was not done yet by the stakeholder that include developing and examinating product concept, bussiness analysis, developing product.Keyword: ecosystem,higher education, innovation,mapping role